Sensory evaluation of food : Principles and practices - Lawless, Harry T. (Food Science Text Series, 2010)
Content: introduction; physiological and psychological foundations of sensory function, principles of good practice; discrimination testing; similarity, equivalence testing and discrimination theory,...